The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/pros.22767
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles and functional associations of endogenous androgen receptor and caveolin-1 in prostate cancer cell lines

Abstract: These data show endogenous AR and Cav-1 mRNA and protein expression is inversely related in PCa cells, with Cav-1 acting on the androgen/AR signaling axis possibly as an AR co-activator, demonstrated by diminished AR genomic activity following Cav-1 knockdown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
(53 reference statements)
1
15
0
Order By: Relevance
“…The latter requires no direct AR functional involvement. In line with previous published results, this study showed that PC3 and DU145 cell lines didn't express AR [34][35][36]. Therefore, possible molecular changes found in either PC3 or DU145 cell lines may represent the AR-independent mechanisms.…”
Section: Discussionsupporting
confidence: 90%
“…The latter requires no direct AR functional involvement. In line with previous published results, this study showed that PC3 and DU145 cell lines didn't express AR [34][35][36]. Therefore, possible molecular changes found in either PC3 or DU145 cell lines may represent the AR-independent mechanisms.…”
Section: Discussionsupporting
confidence: 90%
“…A strong correlation was found between caveolin-1 expression and the presence of venous invasion of HCC samples ( P = 0.02) [20]. In fact, in a series of studies in vivo researchers found caveolin-1 upregulation in several tumors, such as prostate cancer [23], lung cancer [24], and breast cancer [22]. Moreover, some recent papers report caveolin-1 overexpression in HCC and its correlation with prognostic factors [21].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that Cav-1 is involved in various signaling pathways including estrogen receptor, epidermal growth factor receptor (EGFR), Her2/neu, tumor growth factor-β (TGFβ), and mTOR[ 9 ], and serves as an oncogene in lung, breast, and ovarian cancers [ 10 12 ]. In contrast, Cav-1 plays the role of a tumor suppressor in prostate and bladder cancers [ 13 , 14 ]. Bender et al [ 15 ] confirmed that Cav-1 was downregulated in patients with colon cancer, while other studies revealed that Cav-1 was overexpressed in patients with colon adenocarcinoma [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%